Pengembangan Aplikasi Pembelian Voucher Wi-Fi untuk Usaha Rumah Tangga Berbasis Android Menggunakan Pendekatan Rapid Application Development - Priyadi, Restu Fadhilah; Koryanto, Lucky; Faizah, NM (Jurnal Sistem Komputer (SISKOM), 2025)
The rapid development of information and communication technology has significantly impacted various aspects of life, including the management of information and business transactions. Household businesses, particularly those providing home internet services, are also leveraging technology to improve operational efficiency. This research aims to develop an Android-based Wi-Fi voucher purchasing application for household businesses, using the Rapid Application Development (RAD) approach. The application is designed to simplify the Wi-Fi voucher sales process, which was previously handled manually using Microsoft Word, an inefficient method. This application is expected to speed up and streamline transaction processes while reducing reliance on paper usage. Additionally, it will facilitate the management of sales data and accelerate transaction reconciliation. The use of RAD in developing the application enables the creation of an effective and efficient information system in a short period, supporting the smooth operation of home-based internet service businesses.